A translational program that suppresses metabolism to shield the genome - Nathan C. Balukoff (Nature Portfolio, 2020)
Translatome remodelling controls stress-adaptive protein output. Here the authors reveal that in response to stimuli, eIF5A functions as a pH-regulated translation factor that responds to fermentation-induced acidosis affecting cellular metabolism.